Winchester warriors : Texas Rangers of Company D, 1874-1901 - Alexander, Bob, 1943- (Frances B. Vick series ;, 2009)
The Texas Rangers were institutionally birthed in 1874 with the formation of the Frontier Battalion. They were tasked with interdicting Indian incursions into the frontier settlements and dealing with the lawlessness running rampant throughout Texas. This book presents an assessment of Company D and its colorful cadre of Texas Rangers.